PENGENDALIAN MUTU PRODUKSI IKAN SALAI PATIN DI SENTRA PENGOLAHAN PASCA PANEN DENGAN METODE SQC (STATISTIK QUALITY CONTROL)DI DESA KOTO MESJID KECAMATAN KOTO KAMPAR KABUPATEN KAMPAR PROVINSI RIAU - Rahmandinata, Farid; Hamid, Liswar; Marpaung, Rio (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research was conducted in post-harvest processing centers Riau Kampardistrict in order to determine the number of defective products despite having tobear the cost of high quality , and Improve services and Performing continuousquality control , so that the number of defective products which amount 18851.99kg can be minimized becomes smaller for The next production period .Data were collected with the sample data menganmbil production for 4years in a row from2010-2013, and then performed calculations using formulas SQC (StatisticalQuality Control) .The results of this study prove post-harvest processing centers is still not efficient and effective in performing quality control of smoked fishproduction of catfish because they still do lama.Tentunya is the recommended method for using theSQC (Statistical Quality Control ) , in order to control thequality of smokedcatfish production in the desired achieved .Keywords : Quality Control, Method of SQC, Produce, Processing Patin Salai.